Atlas of airborne particles from Kozani area, Northern Greece - Iordanidis, A.; Buckman, J.; Triantafyllou, A. G.; Asvesta, A. (Bulletin of the Geological Society of Greece, 2007)
During a whole year (March 2003 to February 2004), several filters that capture airborne particles were collected from seven sampling sites spread throughout the Ptolemais-Kozani region (Western Macedonia), northern Greece. Environmental Scanning Electron Microscopy (ESEM), coupled with Energy Dispersive X-Ray analysis (EDX) was employed for the characterisation of the airborne particles. A classification of these airborne particles is attempted in this study. Aerosols with various morphological characteristics (angular, irregular, rounded, spherical, spheroidal, acicular), variable size (mostly between 5ßm and 20pm) and composition (aluminosilicates, oxides, carbonates, sulphates, metallic) were recognized. The airborne particulates were also categorized according to their origin. Geogenie, biogenic, anthropogenic (mainly fly ash released from lignite-fired power plants), carbonaceous and metalliferous (mainly iron and copper enriched) were the main categories. A database of characteristic airborne particles from Kozani area is being created using a simple software package, in order to help similar studies in the future.